The causal effects of retirement on mental health: Looking beyond the mean effects - Ingo W.K. Kolodziej; Pilar García-Gómez (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
We analyze the causal effect of retirement on mental health, exploiting differences in retirement eligibility ages across countries and over time using data from the Survey of Health, Ageing and Retirement in Europe. We estimate not only average effects, but also use distributional regression to examine whether these effects are unequally distributed across the mental health distribution. We find unequally distributed protective effects of retirement on mental health. These gains are larger among those above the clinically defined threshold of being at risk of depression. The preserving effects are larger for women, blue collar workers and those in social networks. – – Wir analysieren den kausalen Effekt von Ruhestand auf die psychische Gesundheit, indem wir Unterschiede in den Altersgrenzen für den Rentenzugang zwischen den Ländern und über die Zeit, unter Nutzung des SHARE-Datensatzes (Survey of Health, Agening, and Retirement in Europe), ausnutzen. Wir schätzen nicht nur die durchschnittlichen Effekte, sondern untersuchen auch, ob diese Effekte ungleich über die Verteilung der psychischen Gesundheit verteilt sind. Wir finden ungleich verteilte schützende Wirkungen des Ruhestands auf die psychische Gesundheit. Diese Zugewinne sind größer bei Personen über der klinisch definierten Schwelle ab der das Risiko einer Depression angezeigt ist. Die gesundheitswahrenden Effekte sind größer für Frauen, Arbeiter und Personen mit ausgeprägten sozialen Netzwerken.
Keywords: I10; J14; J26; 330; retirement; mental health; economics of the elderly; distributional regression